Beef Meatballs Quality Prepared with Salt and Phosphate Addition at Various Levels and Time - M. Hatta; E. Murpiningrum (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2012)
Beef meatballs (bakso) need high water-binding or protein extraction properties of fresh meat to improve the emulsification process. The objective of the research was to determine level of combination and addition time of salt (NaCl) and phosphate (STPP) during beef meatballs manufacture. Meat as main ingredients of meatballs obtained from fillet (m.iliopsoas) of Bali cattle. The research was arranged in a Completely Randomized Design with factorial pattern of 2 x 3, and six replications. The first factor was the level of combination of salt and phosphate, i.e. 1. NaCl 4% + STPP 0.3%; 2. NaCl 4 % + STPP 0.5%; 3. NaCl 2% + STPP 0.3%; and 4. NaCl 4 % + STPP 0.5%. The second factor was the addition time of salt and phosphate, i.e. prarigor and postrigor. Parameters of meatballs quality observed were the physical properties (pH and cooking yield) and sensory properties (texture, salt taste, and acceptability). Combination of NaCl 2% and STTP 0,5% added in prarigor and postrigor tend to improve physical properties of meatballs.